Theoretical and Experimental Investigation of the Key Components for a Rotary Desiccant Wheel - Sayed Amir Hossein Zamzamian; Hassan Pahlavanzadeh (Iranian Journal of Chemistry & Chemical Engineering, 2011)
This paper describes the theoretical and experimental investigations of the key components and also the performance analysis of a rotary wheel for using as a solid desiccant dehumidifier and also indirect evaporator cooling system. Solid desiccants have long been used in dehumidification and cooling systems for energy efficiency or reduce electricity. Although many mathematical models on the rotary desiccant wheel have been proposed, the effect of air speed on wheel performance as a momentum equation combined with heat and mass transfer has not been studied. In this study, for the first time the two dimensional mathematical modeling of a desiccant wheel and its numerical simulation using an explicit method considering momentum equation and Ackermann correction factor were described. The results indicated that Ackermann correction factor had a significant effect on performance efficiency. Air stream velocity was one of the most effective parameter on performance and dehumidification rate of wheel. The performance was increased when process air stream velocity decreased. The model suggested the optimum air stream velocity and rotational speed of wheel as 1.86 m s-1 and 10 rad h-1, respectively, obtaining maximum efficiency